Immigration toward Europe; the EU Policy to Challenges of Immigration Crisis - Çay, Furkan (Études sur la Région Méditerranéenne, 2021)
During summer 2015, Europe has received roughly 1.2 million asylum applications, nearly double the number registered in 2014. The vast majority of asylum seekers arrived in Europe through the Mediterranean Sea and arrivals from Turkey to Greece have had put pressure on the Greek-Turkish sea border. Consequently, the EU member states faced various challenges as they did not know how to manage the impacts of the crisis over security, economic, political, and social sphere. This article examines that due to the member states avoided responsibility sharing the situation worsened and the crisis deepened. The article will shed light on the immigration policy challenges of the EU and the EU cooperation with third countries on migration and asylum.